Is a secondary currency essential? On the welfare effects of a new currency - Max Fuchs; Jochen Michaelis (Philipps-University Marburg, School of Business and Economics, 2022)
The coexistence of cash and digital currencies constitutes a system of parallel currencies. This paper tackles the question whether a new (digital) currency is essential: Does a new currency allow for a better resource allocation even if a fully accepted currency is in circulation and still remains in circulation? Using the dual currency search model of Kiyotaki and Wright (1993), we show how the introduction of a secondary currency affects average utility. There is some scope for a welfare improvement, the welfare effect depends on differences in returns and costs, and, in particular, the fraction of cash traders who will be replaced by digital money traders.
Keywords: E41; E42; E51; 330; digital money; dual currency regime; welfare comparison